Features conjugation in Ukrainian Zaporizhzhya-Azov dialects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article investigates verb forms in Ukrainian Zaporizhzhya-azov dialects, established the features of verbal inflection.
Keywords: conjugation; verb forms; Ukrainian Zaporizhzhya-azov dialects